The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1590/s0102-695x2009000600011
|View full text |Cite
|
Sign up to set email alerts
|

Determinação espectrométrica dos flavonóides das folhas de Maytenus (Celastraceae) e de Passiflora (Passifloraceae) e comparação com método CLAE-UV

Abstract: RESUMO:Este trabalho apresenta uma modificação dos procedimentos descritos nas Farmacopéias Francesa e Européia para a análise de flavonoides de Passiflora incarnata L., Passifloraceae, por espectrometria UV-Visível e propõe a sua aplicação na determinação dos flavonoides totais das folhas da espinheira-santa (Maytenus aquifolium Mart. e Maytenus ilicifolia (Schrad.) Planch., Celastraceae) e do maracujá (Passiflora edulis Sims. e Passiflora alata Curtis, Passifloraceae). Os resultados obtidos por espectrometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 9 publications
0
6
1
1
Order By: Relevance
“…Mast showed a high content of phenolic compounds in the form of tannins, flavonoids and flavonols in relation to other species of the genus [11,20,21,22,23], strengthening the evidence that flavonoids are the major components in several species of the genus Passiflora (table 1). To corroborate with these observations, it was previously shown that ExEt had a high amount of phenolic compounds and flavonoids using the HPLC analyzis [24].…”
Section: Phytochemical Characterizationmentioning
confidence: 62%
“…Mast showed a high content of phenolic compounds in the form of tannins, flavonoids and flavonols in relation to other species of the genus [11,20,21,22,23], strengthening the evidence that flavonoids are the major components in several species of the genus Passiflora (table 1). To corroborate with these observations, it was previously shown that ExEt had a high amount of phenolic compounds and flavonoids using the HPLC analyzis [24].…”
Section: Phytochemical Characterizationmentioning
confidence: 62%
“…Hydrated catechin (Sigma) was used for the standard curve (0.1 to 1.0 mg/mL, R=0.99), and absorbance was read at 500 nm. The test to determine the concentration of flavonoids was based on complexation of these compounds with AlCl 3 (Vetec), as described by Chabariberi et al (2009). Hydrated rutin (Sigma) was used for the standard curve (5 to 50 mg/mL, R= 0.99), and absorbance was read at 425 nm.…”
Section: Colorimetric Assaysmentioning
confidence: 99%
“…The remaining aqueous extracted material was lyophilized in an Edwards lyophilizer (Brazil) at 0.9 mbar (-40 ºC). The total flavonoids content of each extract (5 and 2.5 mg/mL) compared to a compensation solution were measured spectrophotometrically in triplicate at 427 nm based upon the formation of a complex with 2% AlCl 3 (Pozzi, 2007;Chabariberi et al, 2009). …”
Section: Passiflora Extracts Preparationmentioning
confidence: 99%
“…Pozzi (2007) and Chabariberi et al (2009) reported on a modification of the spectrometric procedures originally described in the French Pharmacopoeia for the analysis of Passiflora incarnata L., Passifloraceae, flavonoids and proposed its application in the determination of total flavonoids from P. edulis and P. alata leaves. In these studies, the results obtained by a spectrometric procedure were compared to those obtained by high performance liquid chromatography (HPLC-UV).…”
Section: Total Flavonoid Contentmentioning
confidence: 99%
See 1 more Smart Citation